Shape of overvoltage waves arising at lightning strokes to overhead transmission lines - E. Usachev, Aleksandr; M. Yuditsky, Danil; S. Kashaev, Rustem; M. Ba Boraik, Abdulrahman (International Journal of Engineering and Technology, 2018)
This article shows the cause of arising overvoltage thunderstorm waves on overhead transmission lines (OTL) with nanosecond leading fronts. The algorithm is given to estimate the duration of the leading front in the case of back-flashovers from the tower to the phase conductors.Â Â